Plato's Conception of Peace: A Preliminary Exploration. Issue 159 (1st July 2019) - Benitez, Rick
Abstract : This article examines some of the ways in which Plato conveys a concern with peace and what conceptions of peace he has a concern with. I first consider Plato's attitude to war (πόλεμος) and its conventional opposite, peace (εἰρήνη). In this context we find very little concern with peace at all and, by contrast, a somewhat disturbing emphasis on the importance of war. However, if we turn from war to a different type of conflict, faction (στάσις), we find a distinct difference. Plato considers faction unproductive because of the internal divisions it sustains. Yet Plato does not specifically call the opposite of faction 'peace'; instead, he uses terms that have different extensions for us, such as δικαιοσύνη ('justice'). Nevertheless, it is possible to outline a positive Platonic conception of peace by tabling a set a of peace-related terms. I distinguish three categories of terms that describe (1) conditions of peace (or negative peace), (2) dispositions of peacefulness, and (3) relations of peace, where such relations result from the expression of peaceful dispositions. My examination suggests that positive peace, for Plato, is founded on the unity and integrity of character. Only when individuals are at peace with themselves can peace within society be achieved.